ANALISIS STRATEGI READING TIME DALAM MENINGKATKAN MINAT BACA SISWA DI PERPUSTAKAAN SMA AL ISTIQAMAH SIMPANG EMPAT KABUPATEN PASAMAN BARAT - Hayati, Ieka Ratna; Desriyeni, Desriyeni (Scinary, 2023)
This research aims to describe an analysis of the application of the reading time strategy in increasing students' reading interest in the Al Istiqamah Simpang Empat West Pasaman High School library. The type of research is quantitative research with descriptive methods. The data analysis technique in this research is by examining the data, tabulating it using the Arikunto distribution formula. The results of the research show that: (a) the reading interest of students at Al Istiqamah Simpang Empat High School, West Pasaman Regency is still low because there is no strategy that can increase students' reading interest which is applied in a structured and systematic manner and carried out seriously and continuously, ( b) after analyzing the reading time strategy at Al Istiqamah Simpang Empat High School, West Pasaman Regency, it appears that it is still not working properly. This can be seen from the three stages of the reading time strategy (habituation, development and learning) which are still rarely implemented, and (c) the reading time strategy is very likely to be implemented at Al Istiqamah Simpang Empat High School, West Pasaman Regency, where one of the main factors supporting the implementation of the reading time strategy The library of Al Istiqamah Simpang Empat High School, West Pasaman Regency, has a large and up-to-date collection.